CCR2 antagonism in patients with type 2 diabetes mellitus: a randomized, placebo‐controlled study. Issue 11 (25th May 2014) - Di Prospero, N. A.; Artis, E.; Andrade‐Gordon, P.; Johnson, D. L.; Vaccaro, N.; Xi, L.; Rothenberg, P.
Abstract Aims Macrophage recruitment through C‐C motif chemokine receptor‐2 (CCR2) into adipose tissue is believed to play a role in the development of insulin resistance and type 2 diabetes mellitus (T2DM). The objective of this Phase 2 proof‐of‐concept study was to evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of JNJ‐41443532, an orally bioavailable CCR2 antagonist, in patients with T2DM. Methods This was a 4‐week, double‐blind, placebo‐controlled, randomized, multicenter study. A total of 89 patients were randomized to receive either 250‐ or 1000‐mg of JNJ‐41443532 twice daily, 30‐mg of pioglitazone once daily (reference arm), or placebo. The primary endpoint was change from baseline in 23‐h weighted mean glucose (WMG); secondary endpoints included change from baseline in fasting plasma glucose (FPG), insulin resistance (Homeostatic Model Assessment [HOMA‐IR]), insulin secretion (HOMA‐%B) and body weight. Results Absorption of JNJ‐41443532 into the systemic circulation occurred at a median tmax of 2 h, and the mean t½ was approximately 8 h for both doses; plasma systemic exposures increased slightly more than dose‐proportionally. After 4 weeks, reductions in 23‐h WMG and FPG were observed in all treatment groups compared with placebo and were significantly lower for 250‐mg JNJ‐41443532 and pioglitazone. HOMA‐IR was lower for all treatment groups, but significantly lower only for pioglitazone. Conversely, HOMA‐%B was increased for all groups, but significantly increased only for 250‐mg JNJ‐41443532. All groups, including placebo, had decreased body weight over time. There were no clinically significant findings during routine safety assessments and the incidence of treatment‐emergent adverse events was similar across all groups. Conclusions Administration of JNJ‐41443532 resulted in modest improvement in glycaemic parameters compared with placebo, and was generally well tolerated in patients with T2DM.